Recessive dystrophic epidermolysis bullosa results in painful small fibre neuropathy - Calvo, M; Bennett, D (Wiley, 2017)
Small fibres in the skin are vulnerable to damage in metabolic or toxic conditions such as diabetes mellitus or chemotherapy resulting in small fibre neuropathy and associated neuropathic pain (NP). Whether injury to the most distal portion of sensory small fibres due to a primary dermatological disorder can cause NP is still unclear.